Abandon : A Novel - Crouch, Blake (New York : Ballantine Books, 2009)
"On Christmas Day in 1893, every man, woman, and child in a remote mining town will disappear, belongings forsaken, meals left to freeze in vacant cabins, and not a single bone will be found -- not even the gold that was rumored to have been the pride of this town. One hundred and thirteen years later, two backcountry guides are hired by a leading history professor and his journalist daughter to lead them into the abandoned mining town so they can learn what happened. This has been done once before, but the people who went in did not come out. Joining them are a psychic and a paranormal photographer -- the town is rumored to be haunted. Theyve come to see a ghost town, but what they are about to discover is that twenty miles from civilization, with a blizzard bearing down upon them, they are not alone, and the past is very much alive"--
Keywords: Ghost towns -- Fiction; Abandoned mines -- Fiction; Haunted places -- Fiction; Wilderness areas -- Colorado; Fiction; Blizzards -- Fiction; Colorado -- Fiction; Horror fiction; Colorado authors